Analisis Faktor-Faktor Yang Mempengaruhi Kepuasan Kerja Pada Tenaga Kependidikan Unisma Bekasi - Endang Hendrayanti (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2017)
This research aims to determine some factors that affect employee job satisfaction. Object of this research is the administrative and support staff (educational staff) of Unisma Bekasi. The research was conducted in Unisma Bekasi with a population of administrative staff and support staff of 122 employees. In this research, the data will be analyzed using non parametric statistic test analysis, with the perception of matrix performance Important to show some factors that will be priority and the description method that aims to describe the characteristics of the factors that are taking place when the research is done. Furthermore, the data will be analyzed by using mark rank technique from wilcoxon. The results showed that all indicators of employee satisfaction are financial factors, physical factors, social factors and psychological factors are members of the indication that the expected satisfaction during this tend not to match the reality